Kenneth Cobonpue, cutting-edge design from the Philippines to the world (2013)
When it comes to creativity, complicated designs are not always required, we can see how Kenneth has created great real estate products based on creativity in design and innovation in products and materials for manufacturing (such as synthetic rattan), which allow greater durability and moldability in manufacturing.